If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4 = 5x + 4 + -12x + -2 Reorder the terms: -4 + 2x = 5x + 4 + -12x + -2 Reorder the terms: -4 + 2x = 4 + -2 + 5x + -12x Combine like terms: 4 + -2 = 2 -4 + 2x = 2 + 5x + -12x Combine like terms: 5x + -12x = -7x -4 + 2x = 2 + -7x Solving -4 + 2x = 2 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -4 + 2x + 7x = 2 + -7x + 7x Combine like terms: 2x + 7x = 9x -4 + 9x = 2 + -7x + 7x Combine like terms: -7x + 7x = 0 -4 + 9x = 2 + 0 -4 + 9x = 2 Add '4' to each side of the equation. -4 + 4 + 9x = 2 + 4 Combine like terms: -4 + 4 = 0 0 + 9x = 2 + 4 9x = 2 + 4 Combine like terms: 2 + 4 = 6 9x = 6 Divide each side by '9'. x = 0.6666666667 Simplifying x = 0.6666666667
| (-12.8)/(-0.8) | | 4x+2=6x-30 | | 3b+12=5b-40 | | 2/5(5w+10) | | -6(-4)-3y=39 | | x=4+13 | | 7r-5r+2r=5r-r | | 4+4r-1=7r+7-2r | | x=-21+16 | | 50=14+2x | | 4x+2=6x+30 | | -7a-15+-4a+18= | | 4v+24=-3(6v-6)+4v | | 5/4(8) | | 3(-6)+6=2(-6) | | 3p+11p=28 | | 5x-6x=8-2x | | Y=4(-5.25)+25 | | 4x+25=4 | | y/17=-11 | | 4.75=9.5-3/4x | | 9x+4=7+5x | | f/12=12/16 | | 2/3/1/13 | | Y=-3(3)+12 | | 0=9.5-3/4x | | -17/2(-20)+60 | | (a+b/c)(d-e)=f | | -17/4(-20) | | 2x-3=3x+12 | | x+0.02=870 | | 2x+16=42 |